Local Gene Transfer of OPG Prevents Joint Damage and Disease Progression in Collagen-Induced Arthritis. (3rd October 2013) - Zhang, Qingguo; Gong, Weiming; Ning, Bin; Nie, Lin; Wooley, Paul H.; Yang, Shang-You
Abstract : This study examined the influence of osteoprotegerin (OPG) gene transfer on a murine collagen-induced arthritis model. A single periarticular injection of AAV-OPG or AAV-LacZ on the arthritic paw successfully incorporated the exogenous gene to the local tissue and resulted in marked transgene expression in the joint homogenate for at least three weeks. Clinical disease scores were significantly improved in OPG treated mice starting at 28-day post-treatment (P < 0.05 ). Histological assessment demonstrated that OPG gene transfer dramatically protected mice from erosive joint changes compared with LacZ controls (P < 0.05 ), although treatment appeared less effective on the local inflammatory progress. MicroCT data suggested significant protection against subchondral bone mineral density changes in OPG treated CIA mice. Interestingly, mRNA expressions of IFN-g and MMP3 were noticeably diminished following OPG gene transfer. Overall, gene transfer of OPG effectively inhibited the arthritis-associated periarticular bone erosion and preserved the architecture of arthritic joints, and the study provides evidence that the cartilage protection of the OPG gene therapy may be associated with the down-regulation of MMP3 expression.